Neotropical Meliponini: the genus Celetrigona Moure (Hymenoptera: Apidae, Apinae) - Camargo, João M. F.; Pedro, Silvia R. M. (Zootaxa, 2009)
Three new species of Celetrigona are described: C. euclydiana sp. nov., from Acre, Brazil, C. hirsuticornis sp. nov., from Rondônia, Brazil and C. manauara sp. nov., from the northern Amazon. Additional geographic records are provided for C. longicornis (Friese, 1903), the only previously known species; its nest and the male are described and illustrated for the first time. Diagnosis and an identification key for species are provided, which are distinguished by the pattern of pilosity on the antenna.